ADAMTS13 Gene Mutations Influence ADAMTS13 Conformation and Disease Age-Onset in the French Cohort of Upshaw–Schulman Syndrome - Joly, Bérangère S.; Boisseau, Pierre; Roose, Elien; Stepanian, Alain; Biebuyck, Nathalie; Hogan, Julien; Provot, François; Delmas, Yahsou; Garrec, Céline; Vanhoorelbeke, Karen; Coppo, Paul; Veyradier, Agnès; on behalf of the French Reference Center for Thrombotic Microangiopathies (Thrombosis and Haemostasis, 2018)
Background Congenital thrombotic thrombocytopaenic purpura (TTP) or Upshaw–Schulman syndrome (USS) is a rare, life-threatening, inherited thrombotic microangiopathy (TMA). USS is mostly due to bi-allelic recessive sequence variations of the a disintegrin and metalloprotease with thrombospondin type 1 repeats, member 13 (ADAMTS13) gene inducing a severe ADAMTS13 deficiency (activity < 10 IU/dL). In healthy individuals, ADAMTS13 circulates in a folded conformation where CUB domains interact with the spacer domain. The spacer–CUB interaction is abrogated when ADAMTS13 is conformationally activated.Objective This article evaluates the influence of ADAMTS13 sequence variations on both clinical/biological phenotype and ADAMTS13 conformation in USS.Patients and Methods All USS patients from the French registry for TMAs (1 January 2000 to 1 June 2017) were investigated for ADAMTS13 genotype, phenotype (activity, antigen and autoantibodies) and conformation. Clinical records were analysed (inaugural acute TTP and follow-up). Child-onset USS was compared with adult-onset USS.Results Fifty-six USS patients from 51 families (34 child-onset and 22 adult-onset cases) were enrolled. Child-onset USS was characterized by a large panel of ADAMTS13 sequence variations (n = 43), spread all over ADAMTS13 gene and not correlated with either clinical features or plasmatic ADAMTS13 parameters. In contrast, adult-onset USS, consisting exclusively in pregnancy-induced TTP, included a smaller and distinct panel of ADAMTS13 sequence variations (n = 20) because of one mutation (p.Arg1060Trp) present in 82% of patients. ADAMTS13 conformation was studied in 16 USS patients (5 child-onset and 11 adult-onset USS, encompassing 16 distinct ADAMTS13 sequence variations) whose ADAMTS13 antigen levels were detectable: 14 of 16 patients (87.5%) exhibited abnormalities of ADAMTS13 conformation.Conclusion In USS, age-onset defines two entities and ADAMTS13 sequence variations modify ADAMTS13 conformation.
Keywords: ADAMTS13; thrombotic thrombocytopenic purpura; Upshaw–Schulman syndrome; von Willebrand factor; rare disease